2015
DOI: 10.1016/j.applanim.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

What can inactivity (in its various forms) reveal about affective states in non-human animals? A review

Abstract: Captive / domestic animals are often described as inactive, with the implicit or explicit implication that this high level of inactivity is a welfare problem. Conversely, not being inactive enough may also indicate or cause poor welfare. In humans, too much inactivity can certainly be associated with either negative or positive affective states. In non-human animals, however, the affective states associated with elevated or suppressed levels of inactivity are still not well understood. Part of the complexity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 256 publications
0
78
0
Order By: Relevance
“…When under sub-optimal conditions, horses can develop an apathetic state, related to depressed-like syndromes [28,29,52,65,92], characterized by sensorial withdrawal (visual and tactile [28,92]) and a general flattened posture [92]. This syndrome, first identified for horses working in developing countries [28,30], has also been identified in riding school horses in France [35,52,92], and is related to the occurrence of health (work-related wounds [29,30], low BCS and lameness [28]), physiological (depressed cortisol levels [92]) and behavioural/psychological (anhedonia: [52]) disorders. However, Burn et al [65] found only a moderate inter-observer agreement for their horse population.…”
Section: Modifications Of Horses' Behavioural Repertoirementioning
confidence: 99%
“…When under sub-optimal conditions, horses can develop an apathetic state, related to depressed-like syndromes [28,29,52,65,92], characterized by sensorial withdrawal (visual and tactile [28,92]) and a general flattened posture [92]. This syndrome, first identified for horses working in developing countries [28,30], has also been identified in riding school horses in France [35,52,92], and is related to the occurrence of health (work-related wounds [29,30], low BCS and lameness [28]), physiological (depressed cortisol levels [92]) and behavioural/psychological (anhedonia: [52]) disorders. However, Burn et al [65] found only a moderate inter-observer agreement for their horse population.…”
Section: Modifications Of Horses' Behavioural Repertoirementioning
confidence: 99%
“…The results show clear differences between rats experiencing complex and novel housing also been demonstrated to denote good welfare in laboratory rats (Manser, 1992;Blanchard et al, 1995;Haller et al, 1998;Tsai et al, 2003;Ćœivkovic et al, 2005). Similarly, aggression, non-aggressive social interaction, awake non-active behaviours, away from enrichment, underneath hopper and audible vocalizations have been used to judge the welfare of laboratory rodents with elevated levels being indicative of a generally compromised welfare state (Adams, 1977;Vivian and Miczek, 1993;Marashi et al, 2004; see also Fureix and Meagher 2016). One reason why non-aggressive social interaction may be related to poor welfare is that it may induce aggressive responses in laboratory rodents by increasing the chance that two rats in a cage meet or come in to direct contact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Animals have also been known to decrease general activity when threatened by predators or when they feel danger [15] . While inactivity or its lack thereof is not usually a definitive indicator of an animal's welfare state [16] , it could point the farmer in the right direction so that further investigations can be carried out on the animal concerned.…”
Section: Introduction mentioning
confidence: 99%